Understanding Generational Perceptions: The Influence of Free Service towards Premium Service Purchase Intention in OMS Platform - Andryani, Hana Aiko; Chaerudin, Rendra (Journal of Business and Management, 2021)
The Online Music Streaming (OMS) platform is one of the biggest contributors towards music industry’s revenue. However, the revenue stream of OMS platform is limited into two sources; premium service and paid advertisements. Most of the users are using the free service of the platform and they are spread between three consecutive generations; generation X, Y, and Z. This research purpose is to (1) identify the difference in how each generation’s age and behavior affect their perceptions towards the free OMS platform; (2) determining its impact towards the intention to convert into premium user. This research involved 402 respondents from Indonesia and is analyzed using the SEM-PLS method. The results show that only generation X has different influence towards their perceptions on OMS platform. Generation Y and Z has significant influence towards their perceived usefulness, perceived enjoyment, and perceived trust. However, the perceived usefulness is the only perception that has significant impact towards their purchase intention. Meanwhile, generation X was found to have insignificant influence towards their perceived trust and none of the perceptions have a significant influence towards their purchase intention of premium service in OMS platform. This research is expected to benefits the OMS Industry and future studies. Keywords : Consumer Perception, Digital Platform, Generational Cohorts, Music Streaming, PartialLinear Regression, Purchase Intention.